Antidepressant Drug Discovery and Development: Mechanism and Drug Design Based on Small Molecules. Issue 5 (30th March 2022) - Yao, Chuansheng; Jiang, Xiaoying; Ye, Xiang‐Yang; Xie, Tian; Bai, Renren
Abstract: Depression is one of the most prevalent mental diseases and a primary cause of disability worldwide with high incidence and high recurrence. The current deterioration of the COVID‐19 epidemic also pushes up the incidence of depression. Nevertheless, the currently available treatments remain inadequate response and limited efficacy. Therefore, discoveries of more potent and safer antidepressant drugs are urgently needed. In this review, the current potential physiological and pathological mechanisms of depression, and the clinical research progresses of candidate drugs as well as the recent advances in small‐molecule drug discovery for potential treatments of depression are systematically summarized. More importantly, the structure–activity relationships of compounds from different classes, the statistical analysis of the blood‐brain barrier permeability, the pharmacological targets, and the in vivo models are comprehensively discussed. Further insights on antidepressant drug discovery are also analyzed from multidimensional perspectives. Abstract : Depression is one of the most prevalent mental diseases. The physiological and pathological mechanisms, the clinical research progress, and recent advances in small‐molecule drug discovery for treatments of depression, and the structure–activity relationships of the targeted compounds are summarized and reviewed.